Can diet niche partitioning enhance sexual dimorphism?. Issue 12 (18th December 2022) - Bauld, Joshua T.; Abernethy, Katharine A.; Newton, Jason; Lehmann, David; Jones, Isabel L.; Bussière, Luc F.
Abstract: Classic evolutionary theory suggests that sexual dimorphism evolves primarily via sexual and fecundity selection. However, theory and evidence are beginning to accumulate suggesting that resource competition can drive the evolution of sexual dimorphism, via ecological character displacement between sexes. A key prediction of this hypothesis is that the extent of ecological divergence between sexes will be associated with the extent of sexual dimorphism. As the stable isotope ratios of animal tissues provide a quantitative measure of various aspects of ecology, we carried out a meta‐analysis examining associations between the extent of isotopic divergence between sexes and the extent of body size dimorphism. Our models demonstrate that large amounts of between‐study variation in isotopic (ecological) divergence between sexes is nonrandom and may be associated with the traits of study subjects. We, therefore, completed meta‐regressions to examine whether the extent of isotopic divergence between sexes is associated with the extent of sexual size dimorphism. We found modest but significantly positive associations across species between size dimorphism and ecological differences between sexes, that increased in strength when the ecological opportunity for dietary divergence between sexes was greatest. Our results, therefore, provide further evidence that ecologically mediated selection, not directly related to reproduction, can contribute to the evolution of sexual dimorphism. Abstract : Theoretical and empirical work suggests that between‐sex competition for resources plays a role in the evolution of sexual dimorphism. We investigated this concept by analyzing cross‐species relationships between the extent of sexual dimorphism and published sex differences in tissue stable isotope values, which are a proxy of dietary differences. We found that sexual dimorphism is related to sex differences in trophic level, in directions and contexts consistent with those expected if resource competition is involved in the evolution of sexual dimorphism.